Islamic Boarding School Management In Cultivating The Entrepreneurial Spirit Of Students - Ahmad Shirojul Munir; Nur ‘Azah (Pondok pesantren As-salafiyah As-Safi'iyyah, 2026)
This study aims to describe the planning, implementation and evaluation in fostering the entrepreneurial spirit of students at the Al-Urwatul Wutsqo Islamic Boarding School in Jombang. This study uses a qualitative approach with a case study type. Data collection techniques are carried out through observation, interviews, and documentation. Data analysis techniques consist of data reduction, data display, and conclusion drawing. The validity of the data was tested using source, time, and technique triangulation. The results show that: (1) Entrepreneurial planning is carried out by preparing productive business units such as agriculture, longan plantations, cattle farming, fish cultivation, furniture making, and barbershop services; (2) Implementation involves both theoretical entrepreneurship education and direct practice by the students; (3) Evaluation is conducted to measure the achievement of each unit's program implementation. These business units contribute to student self-reliance, skill improvement, and pesantren financial support. Therefore, pesantren management plays an essential role in developing entrepreneurial spirit as a provision for students to live independently in modern society.